Islamic youth associations in Italy. Dimensions and practices of citizenship - Martina Crescenti (University of Bologna, 2023)
The essay presents an analysis of the definition and enactment of citizenship by second-generation Muslim youth, active members of Islamic youth associations in Italy, whose path to recognition as citizens is hindered at the institutional and social levels. Based on qualitative research conducted between 2020 and 2021, we analyze 28 individual interviews with young activists on which, on the one hand, we investigate the experiences of racist and Islamophobic discrimination that drive young people to mobilize in associations, and on the other hand, how they define the concept of citizenship. This concept is also delineated through the analysis of two recreational and playful events open to the entire population and promoted by one national association in particular, Giovani Musulmani d'Italia. Through the two events, conceived as practices of citizenship, an idea of belonging to the Italian context based on dialogue and mutual knowledge is shown, in an already multicultural and multireligious country, in which the young Muslim born and schooled person acts as a citizen, although without formal recognition.